REVITALISASI BUDAYA LOKAL MELALUI TARI KREASI BERBASIS PERMAINAN JARAK-JARAK ANTUM DI PROVINSI JAMBI - Siti Mutia Rusmana; Septiana Dwi Astuti; Retno Sintya Dewi; Leni Khusniah; Nessa Syahrirra; Eka Wulandari; Intan Annidya Putri; Hanifa Yuniastuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research focuses on revitalizing local culture through the development of creative dances based on the traditional game of Jarak-Distance Antum in Jambi Province. The traditional game of Distance-Distance Antum which has the values of togetherness, mutual cooperation, and sportsmanship, has been adapted into a form of creative dance. The purpose of this research is to preserve and reintroduce local cultural values to the younger generation through dance. This study uses a qualitative descriptive method, with data collection techniques in the form of observation and interviews. The data obtained was analyzed to identify cultural elements, movements, and values contained in the Antum Distance game which was adapted into the form of creative dance. Cultural revitalization through creative dance is expected to be an effective means of maintaining cultural heritage in the midst of the challenges of globalization and modernization. Thus, the traditional game-based creation dance of the Antum Distance not only serves as entertainment, but also as a tool for sustainable cultural education.